Conceptualizing recovery capital for older adults with substance use disorders. Issue 4 (2nd October 2021) - LaBarre, Charles; Linn, Braden K.; Bradizza, Clara M.; Bowen, Elizabeth A.; Stasiewicz, Paul R.
ABSTRACT: The older adult population in the United States is projected to grow significantly due to improvements in healthcare and sustained population growth. Adults aged 65 and older experience unique risks for, and consequences of, substance misuse. This Endpage applies recovery capital theory to outline the distinctive physical, social, human, and community and cultural forms of recovery capital for older adults. Based on this conceptualization, we provide directions for examining recovery from substance use disorders among older adults.